High temperature properties of the Cr-Nb-Al-N coatings with increasing Al contents - Li, W. Z. (2013)
Cr-Nb-Al-N coatings with Al content from 0 to 12 at.% were deposited by d.c. reactive magnetron sputtering. The coatings were annealed in protective atmosphere at 800 and 900 °C for 1 h and exposed to air at 800, 900 and 1200 °C for different times. The chemical composition, structure, microstructure, hardness and adhesive/cohesive strength of the coatings, in as-deposited and annealed conditions, were investigated and the oxidation resistance was evaluated. As expected, the Al content increased gradually in the coating with increasing power density in the Al target; nitrogen was kept approximately constant. All coatings exhibited columnar cross section morphology and fcc NaCl-type B1 phase structure. After thermal annealing, an increase in the grain size and a decrease in the lattice parameter were observed, which led to either a decrease in the hardness or lower adhesion/cohesion strength than the as-deposited coatings. The onset oxidation temperature was approx. 900 °C for all coatings. High Al content coatings showed minimum oxidation when exposed to 800 °C for 2 h and to 900 °C for 0.5 h in air. The Al-free and low Al coatings exhibited lower oxidation resistance; Cr2O3 and CrNbO4 coexisting together although signs of the cubic nitride phase were still detected. The increase of Al was beneficial to the improvement of the thermal stability and oxidation resistance of the Cr-Nb-Al-N coatings.